Hydrogen production via glycerol dry reforming over nickel catalyst supported on sio2 and Al2O3 modified by La - Farahani, Sarajuddin (2015)
Currently, energy has become the most demand for human needed. The utilization of future energy that is clean and sustainable becomes increasingly urgent because of dwindling petroleum reserves and mounting environmental concerns that are associated with fossil fuel. Hydrogen has been considered as the most suitable alternative for future energy aiming to reduce the dependence on fossil fuel and carbon based emission. Previously, non-renewable resources mainly coal, fossil fuel, petroleum coke, and petroleum residues has been widely used as the main feedstock for syngas (H2 and CO) production. However, due to the various factors such are global warming, the unstable price and availability of petroleum-based oil as well as the environmental pollution, the desirability towards biomass (glycerol) as the alternative energy feedstock has attract the world’s attention. Glycerol which a by-product of biodiesel production is one of the most promising renewable sources associated environmental impacts from the usage of the fossil fuels in which it minimal carbon dioxide (CO2) emission and more preferable in fuels production. In recent years, the production of hydrogen from glycerol via steam reforming widely investigated, only a few studies on dry reforming with CO2. Therefore, this project was attempted to study the production of hydrogen via glycerol dry reforming over nickel (Ni) catalyst supported on silica oxide (SiO2) and alumina (Al2O3) modified with lanthanum (La). This works aims to synthesis, characterize, and screening Ni catalyst supported on SiO2 and Al2O3 with promoted in La solution using various techniques such are Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) analysis , Mastersizer 2000 Ver.5.60 and elemental analysis. The catalyst characterization includes their porosity, structure, crystalline behaviour, and a physiochemical property is investigated. It shows that the promoted catalyst possessed smaller metal crystalline size, hence higher metal dispersion compared than both Ni/Al2O3 and Ni/SiO2 catalyst. In addition, the particle size distribution measured by Mastersizer measurement for promoted alumina catalyst gave higher size distribution which about 0.452 m2/g compared than silica oxides support. The reaction studies for syngas production at T=973 K for 3 hour reaction time with the inlet flowrate and carbon to to glycerol ratio is 0.03 ml/min and 1 had successfully produced H2 with glycerol conversion and H2 yield that peaked at 5.8% and 28% respectively over 3% La content. The catalyst screening shows that the alumina support gave excellent catalytic performance compared than silica oxide due to the larger surface area and smaller crystallite size that ensured accessibility of active catalytic area.